Economies of Scale, Technical Change, and Total Factor Productivity Growth of the Saudi Electricity Sector. - Al-Mahish, Mohammed (International Journal of Energy Economics and Policy, 2017)
This paper aims to accomplish two objectives. The first is to extend the existing method of total factor productivity growth decomposition by incorporating network characteristics. The second objective is to empirically evaluate technical change and productivity of the Saudi electricity sector. The results show that the Saudi electricity sector operates under the presence of economies of output density, economies of customer density, and diseconomies of scale. The technology used in the Saudi electricity sector is a cost saving technology. It is characterized as fuel using, capital neutral, and energy saving technology. The estimated average technical change term is positive. It indicates a cost increase during the timeframe of this study. The estimated average total factor productivity growth is positive using both the proposed and existing method. Compared with the proposed method, the existing method overestimated total factor productivity growth of the Saudi electricity sector. Furthermore, the paper estimated an optimal scale of output to be almost 11 percent larger than the maximum output level generated by the Saudi Electricity Company. The paper concludes that the Saudi Electricity Company needs to expand its size to reach the optimal output level. Keywords: Energy; Total factor productivity growth; Economies of scale; Technical change JEL Classifications: Q40, D24, O33, L25, L94